1991
DOI: 10.1159/000461307
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Red Blood Cell Preservation: 4. Plasma Vesicle Hemoglobin Exceeds Free Hemoglobin

Abstract: Studies were designed to find out how much of the plasma hemoglobin (Hb) in whole blood was in microvesicles and how much was free Hb after 21 days of storage in citrate-phosphate-dextrose anticoagulant and to determine the effect of the plasticizer, di-(2-ethylhexyl) phthalate (DEHP). The total plasma Hb in polyolefin (PO) containers without DEHP was much higher than in polyvinyl chloride (PVC) with the plasticizer (p = 0.004). Less than 30% of the Hb was in free solution in either type of container. The addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 4 publications
0
45
0
Order By: Relevance
“…4). 106 We saw no differences in the size of the vesicles in either preparation; it is possible, however, that the nanovesicles (diameter, 60 nm), first reported by Allan and associates 54 were centrifuged down with the microvesicles under the conditions we used.…”
Section: Microvesiculation In Rbc Maturation and Agingmentioning
confidence: 65%
“…4). 106 We saw no differences in the size of the vesicles in either preparation; it is possible, however, that the nanovesicles (diameter, 60 nm), first reported by Allan and associates 54 were centrifuged down with the microvesicles under the conditions we used.…”
Section: Microvesiculation In Rbc Maturation and Agingmentioning
confidence: 65%
“…It has been suggested that microvesiculation contributes more to the increase in the plasma Hb occurring during storage than free Hb. 25 Based on our microscopic data, it seems probable that the plasma Hb found in prolonged liquid storage is not so effectively enclosed into vesicles, but it can be released from them.…”
Section: Structural Degeneration Of the Vesiclesmentioning
confidence: 83%
“…The adenine nucleotides are better maintained in RAS2 than in SAGM and the spontaneous storage hemolysis is significantly lower from the second week of storage. It has recently been demonstrated [26] that most of the free he moglobin in stored blood originates from microvesicles. Microvesiculation implies an irreversible loss of mem brane cholesterol and phospholipids, occurring when mi crovesicles are budded off from RBC spicules (mainly in echinocytes-3 and echino-spherocytes).…”
Section: Discussionmentioning
confidence: 99%